Pengaruh Faktor Internal Dan Faktor Eksternal Terhadap Non Performing Financing (NPF) Pada Pembiayaan Bank Umum Syariah - Ainiah, Pocut; Sriyana, Jaka (Jurnal Ilmiah Ekonomi Islam, 2024)
This research aims to analyze the influence of internal factors and external factors of Sharia Commercial Banks on the NPF for murabahah financing, NPF for musyarakah financing, NPF for mudharabah financing, NPF for ijarah financing, NPF for istishna financing, and NPF for qardh financing. The research method used is quantitative research using secondary data from Bank Muamalat Indonesia, Bank BCA Syariah, Bank Panin Syariah, Bank Bukopin Syariah, Bank Mega Syariah, and Bank Victoria Syariah, all of which are the results of financial reports published by the OJK during the quarterly period. 1 of 2013 to the fourth quarter of 2022. The results of this research are that internal factors and external factors have an influence on NPF in murabahah, musyarakah and istishna financing in sharia commercial banks. Meanwhile, the NPF for mudharabah, ijarah and qardh financing is not influenced by internal and external factors in Islamic commercial banks.